ANALYSIS OF THE CONTRIBUTION OF SWALLOW(COLLOCALIA FUCIPHAGA) BUSINESS INCOME TO THE INCOME OF FARMER FAMILIES IN PASANGKAYU VILLAGE - Zulfikar; Muh Arifin Fattah; Isnam Junais (Universitas Muhammadiyah Makassar, 2026)
Swiftlet nest farming is an economic activity within the livestock sector that offers substantial and sustainable profits for business actors. This study aims to analyze the income generated from swiftlet nest farming and its contribution to the income of farming families in Pasangkayu Village, Pasangkayu Sub-district, Pasangkayu Regency. The sample utilized in this study consisted of 18 swiftlet farming families who met the specified criteria, drawn from a population of 93 farmers using a purposive sampling method. The data analysis methods employed in this study were income analysis and income contribution analysis. The results revealed that the average net income of the swiftlet nest business over a one-year period in Pasangkayu Village was IDR 48.530.218/year. This figure represents the net profit obtained by the farming families, derived from the difference between total revenue and total production costs. Meanwhile, the average total income earned by the farming families amounted to IDR 107.410.218. The contribution of the swiftlet nest business to the total income of the farming families was 45.18%. This value indicates that the swiftlet nest business provides a highly significant and strategic contribution, even serving as the primary pillar in supporting the family economy compared to other main occupations